دور القطاع الخاص في نمو الاقتصاد العراقي للمدة (2004- 2020) دراسة تحليلية قياسية - غفور, نرمين معروف; عبدالله, سامان محمد (Sulaimani Journal for Humanities, 2022)
The main objective of this research is to analyze the reality of the private sector in the Iraqi economy and measure the extent of its contribution to achieving growth, in light of the available data for the period (2004 - 2020), and to achieve this goal, the descriptive and standard analysis method was used using the (9EViews) program. The research reached a number of conclusions, the most important of which is that the private sector, despite its positive impact on the rate of economic growth, but its role in economic activity was weak during the research period. Its contribution to the generation of GDP and fixed capital formation remained low in most years, and it may be The reason for this is the continuation of the dominance of the government sector financed by crude oil export revenues over all economic activities and activities.. This requires setting policies and programs supportive of the private sector and looking at the role of this sector as a partner in the process of economic growth, by strengthening the general economic climate and creating a stable and attractive environment for investments, while expanding and renewing the infrastructure that supports economic activities and stimulates the orientations of the private sector, Local and foreign towards the establishment of various productive projects to ensure the restructuring of sectors and increase economic diversification.